2020
DOI: 10.2147/hiv.s260908
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Ear Nose and Throat (ENT) Manifestations Among HIV Seropositive Patients at a Tertiary Hospital in Northern Tanzania: A Descriptive Cross-Sectional Study</p>

Abstract: Background: To date, HIV/AIDS remains a threat of the 21st century. The overall rate of new HIV infection continues to decline in several countries, but there is still a remarkable burden of disease seen in sub-Saharan Africa. Several studies observed that 70% to 90% of HIV-infected patients present with ear, nose and throat symptoms. The aim of this study was to identify the magnitude of ENT manifestations among HIV-infected patients attended HIV clinics at KCMC based on age, sex, and CD4 count. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…We identified that most cases were found in female patients, who represented 58.1% of all hospitalizations analyzed. This finding is consistent with the results of the study published by Shija et al [ 5 ], which showed a 67.5% female predominance in ENT pathologies. This distribution reflects the global demographic ratios of HIV infection, where according to the Joint United Nations Programme on HIV and AIDS (UNAIDS), in 2022, more than 53% of people living with HIV globally were female [ 10 ], and this is particularly true for Romania as well, by contrast with most Central and Western European countries.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We identified that most cases were found in female patients, who represented 58.1% of all hospitalizations analyzed. This finding is consistent with the results of the study published by Shija et al [ 5 ], which showed a 67.5% female predominance in ENT pathologies. This distribution reflects the global demographic ratios of HIV infection, where according to the Joint United Nations Programme on HIV and AIDS (UNAIDS), in 2022, more than 53% of people living with HIV globally were female [ 10 ], and this is particularly true for Romania as well, by contrast with most Central and Western European countries.…”
Section: Discussionsupporting
confidence: 94%
“…Published data show that a large share of people living with HIV experience ear, nose and throat (ENT) manifestations at some point during the course of their HIV infection and most often during the periods of immune suppression [ 5 ]. Although the clinical spectrum of ENT manifestations is very varied, sinus [ 5 ] and otic [ 6 ] involvement are among the most common. Sinusitis and otitis have been shown to occur more frequently in patients with infection who also have a CD4+ T-cell level below 200 cells/μL.…”
Section: Introductionmentioning
confidence: 99%